A Mouse Model of Vascularized Skin Transplantation. Issue 5 (May 2017) - Ding, Jianke; Su, Yingjun; Liu, Shiqiang; Yang, Yang; Zhou, Bo; Yu, Zhou; Xiao, Bo; Guo, Shuzhong
Abstract : Background: Allogeneic skin tissues are highly antigenic and induce intensive immune rejection after composite tissue allotransplantation. Mouse models have advantages in mechanistic studies of immune rejection. However, due to technical challenge in vascular anastomosis with suture technique, mouse vascularized skin allotransplantation models are not widely used in studies of immune rejection. Therefore, the authors propose vascular anastomosis through cuff technique during allotransplantation of mouse donor free groin skin flaps to either recipient inguinal or cervical site. Methods: Free groin skin flaps from BALB/c or C57BL/6 donor mice were transplanted to the groin (inguinal vascularized skin transplantation [IVST]) or to the neck of recipient sites (cervical vascularized skin transplantation [CVST]) of C57BL/6 mice. A nonsuture cuff technique was utilized to anastomose the donor vessels with either femoral vessels in IVST recipients or common carotid arteries and external jugular veins in CVST mice. Immunosuppressant drugs were used in the allogeneic skin group. Results: The overall success rate was higher in the CVST (88.5%) when compared with the IVST (78.9%). Total operation time in CVST mice lasted 96 minutes (95% confidence interval, 92–101 minutes) that was shorter than that for IVST mice (136 minutes, 95% confidence interval, 127–176 minutes; P < 0.01). Complications, such as hindlimb necrosis and self-mutilation, were observed in IVST mice. Rapamycin (3 mg/kg, daily) significantly prolonged vascularized skin allografts survival with median survival time of 80 days. All syngeneic grafts survived for more than 80 days. Conclusions: We developed a novel mouse vascularized skin transplantation model that is feasible for the study of clinically relevant skin rejection and tolerance.